2013
DOI: 10.1177/0741088313491713
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Chains as a Method for Examining the Teaching and Learning of Argumentative Writing in Classrooms

Abstract: We propose “instructional chaining” as an analytic method for capturing and describing key instructional episodes enacted by expert writing teachers to foster the recontextualization over time of the social practices of argumentative writing through process-oriented instructional approaches. The article locates instructional chaining within a sociocultural framework and argues for conceptualizing learning to write as the recontextualization of social practices of writing in classroom settings. To illustrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Context for data sources. We asked each teacher to name a significant event during instruction during our postobservation debriefings and used those events to create instructional chains (VanDerHeide & Newell, 2013) to represent the 150 min most critical to helping students be successful on their respective teacher-sponsored summative assessments (see Appendices B and C in the Online, supplementary archive). We selected events in which Ms. Houston's class analyzed the implied argument of an editorial cartoon where Santa appears ready to cut the head off a Thanksgiving turkey (Stahler, 2011) and in which Mr. Clark's class analyzed a sketch of a lunchroom murder (Hillocks, 2011) to determine the perpetrator.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Context for data sources. We asked each teacher to name a significant event during instruction during our postobservation debriefings and used those events to create instructional chains (VanDerHeide & Newell, 2013) to represent the 150 min most critical to helping students be successful on their respective teacher-sponsored summative assessments (see Appendices B and C in the Online, supplementary archive). We selected events in which Ms. Houston's class analyzed the implied argument of an editorial cartoon where Santa appears ready to cut the head off a Thanksgiving turkey (Stahler, 2011) and in which Mr. Clark's class analyzed a sketch of a lunchroom murder (Hillocks, 2011) to determine the perpetrator.…”
Section: Data Sourcesmentioning
confidence: 99%
“…While research has addressed the epistemological values students attribute to the role of argumentation as a mode of reasoning (Kuhn, Wang, & Li, 2011), as well as how students’ argumentative practices are influenced by their learning contexts (Evagorou & Osborne, 2013; Hillocks, 2011; Kuhn, Hemberger, & Khait, 2016), little is known about the extent to which students’ tacit understandings of fundamental concepts such as fact and opinion influence their development as writers of academic argument. VanDerHeide and Newell (2013) posit a view of learning to write arguments as a process of recontextualizing argumentative practices over time and across contexts. This view follows from an understanding that students do indeed draw upon tacit understandings of what counts as an argument and what makes an argument effective.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…As mentioned previously, the study took place in the context of a larger design-based research project. A number of important studies of literacy instruction have been conducted in the context of design-based research involving highly regarded teachers (e.g., Applebee, Langer, Nystrand, & Gamoran, 2003;Bloome, 2015;Langer, 2001;Newell et al, 2014;VanDerHeide & Newell, 2013). In this tradition and with this broader research agenda in mind, observed teachers were recruited and selected as potential long-term partners.…”
Section: Sample Recruitment and Selectionmentioning
confidence: 99%
“…These studies have suggested that instruction varies considerably, even when teachers are enacting the same intervention. A rare study of argumentation practices absent implementation of a specific intervention likewise found significant variation in how teachers understood and taught argumentative writing (Bloome, ; Newell et al., ; VanDerHeide & Newell, ). Thus, although studies have yielded important insights about variation in argumentation teaching and learning, we know of no studies to date that have examined the wide range of argumentation activities and tasks offered to middle and high school students across subject areas, absent implementation of a specific intervention.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%